Prenatal sonographic detection of birth defects in 18 hospitals from South America - Campaña, Hebe (2010)
Objective. The purpose of this study was to assess the accuracy of prenatal sonographic diagnosis of birth defects and the gestational age at detection according to the health insurance schemes of mothers in 450 malformed neonates from 18 South American hospitals on the basis of prenatal sonographic records. Methods. Between July 2000 and December 2003, 18 hospitals included in the Latin American Collaborative Study of Congenital Malformations (13 from Argentina [8 public and 5 nonpublic], 3 from Brazil [2 public and 1 nonpublic], 1 from Chile [nonpublic], and 1 from Venezuela [public]) voluntarily participated in this prospective observational study, recording fetuses with sonographically detected malformations. Prenatal sonographic descriptions of anomalies were compared with those recorded at birth. Results. Of 812 anomalies detected at birth, 457 had been prenatally detected (detection rate, 56.3%; 95% confidence interval, 52.8%-59.8%). Before 24 gestational weeks, anencephaly had the highest detection rate. Cleft lip and clubfoot were more easily detected when associated with other anomalies. The detection rates for central nervous system and renourinary malformations were greater than 80%. Detection rates between both health insurance schemes (public and nonpublic) did not show significant differences, but anencephaly, spina bifida, renourinary defects, and cleft lip with or without cleft palate were detected earlier in patients from nonpublic rather than in public hospitals. Conclusions. For specific anomalies, South America shows similar levels of prenatal sonographic detection as developed countries. Detection rates during pregnancy were similar for public and nonpublic hospitals, whereas cases were diagnosed earlier in patients from nonpublic hospitals.